Evaluasi Tingkat Pengungkapan Laporan Keberlanjutan (Studi Kasus pada Perusahaan Peleburan Tembaga) - Nirmalasari Dwi Cahyaningrum; Evony Silvino Violita (Owner : Riset dan Jurnal Akuntansi, 2023)
The issue of sustainability has begun to become the focus of worldwide attention in all aspects. The copper smelting industry can be said to be one of the causes of emergences of environmental and social problems so the sustainability strategy becomes an essential thing for this industry This research is designed to examine the sustainability reporting issued by one of the copper smelting industry in Indonesia, which is the first time the company has issued a sustainability report in 2021 which is after the enactment of POJK No. 51/POJK.03/2017. The method used in this research is a case study by doing content analysis qualitative where content analysis is performed on the information published in the sustainability reports disclosure to use Surat Edaran Otoritas Jasa Keuangan (SEOJK) number 16 and also the Global Reporting Initiative (GRI) as assessment parameters, as well as interviews with a corporate secretary, become supporting data. Then, this research fills in the inner gap empirical approach to analyze the sustainability report disclosure within the company smelting industry. The results of this study show that the revelation of the company's sustainability report in 2021 has fulfilled the regulations by POJK No. 51/POJK.03/2017 However, in terms of the quality of the contents of each component, it is still not explained comprehensively. One of the copper smelting industries in Indonesia's sustainability disclosure includes 35 indicators in the GRI standard.